2021
DOI: 10.1016/j.fochx.2021.100161
|View full text |Cite
|
Sign up to set email alerts
|

Caferana seeds (Bunchosia glandulifera) as a new source of nutrients: Evaluation of the proximal composition, solvent extraction, bioactive compounds, and δ-lactam isolation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…They were also analyzed the seeds of Bunchosia glandulifera, evidencing the presence of phenolic compounds, caffeine, and δ-lactam, which they associated with the beneficial effects on mental health described by populations consuming this product [140]. According to Lee et al, identified a new nitrophenyl glycoside, ginkgonitroside, which they isolated from Ginkgo biloba leaves.…”
Section: Food Waste and Novel Bioactive Compoundsmentioning
confidence: 99%
“…They were also analyzed the seeds of Bunchosia glandulifera, evidencing the presence of phenolic compounds, caffeine, and δ-lactam, which they associated with the beneficial effects on mental health described by populations consuming this product [140]. According to Lee et al, identified a new nitrophenyl glycoside, ginkgonitroside, which they isolated from Ginkgo biloba leaves.…”
Section: Food Waste and Novel Bioactive Compoundsmentioning
confidence: 99%
“…At the same time, the growing attention to the environment has led to the study of new procedures for reducing chemical additives and waste in the food sector (Pellegrini et al ., 2006; Maltese et al ., 2009; Fraga et al ., 2021; Liu et al ., 2021; Mesquita et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%